Landmark - Ewing, William A. (New York, NY : Thames & Hudson, 2014)
Photographers include: Darren Almond, Dag Alveng, Benoit Aquin, Olivo Barbieri, Olaf Otto Becker, Daniel Beltr, Jonas Bendiksen, Mathieu Bernard-Reymond, Peter Bialobrzeski, Justine Blau, Robert Bourdeau, Sonja Braas, Matthew Brandt, Olaf Breuning, Edward Burtynsky, Luca Campigotto, Alexandra Catiere, Philippe Chancel, Lynne Cohen, Scott Conarroe, Stéphane Couturier, Raphaël Dallaporta, John Davies, Robert Davies, Gerco De Ruijter, Susan Derges, Mitch Dobrowner, Natan Dvir, Mitch Epstein, Elger Esser, Susan Evans, J. Henry Fair, Nicolas Faure, Joan Fontcuberta, Lee Friedlander, Matthieu Gafsou, Andreas Gefeller, John Gerrard, Ori Gersht, Georg Gerster, Andreas Gursky, Beate Gütschow, Leonora Hamill, Rob Hann, Naoya Hatakeyama, Lois Hechenblaikner, Mishka Henner, Dan Holdsworth, Pieter Hugo, Axel Hütte, Geoffrey James, Vincent Jendly, Florian Joye, Nadav Kander, Michael Kenna, Gabor Kerekes, Mark Klett & Byron Wolfe, Peter Knapp, Ellen Kooi, Ivar Kvaal, An-My Lê, Michael Light, Liu Xiaofang, Pablo López Luz, Marcus Lyon, Patricia Macdonald, Alex Maclean, David Maisel, David Malin, Sally Mann, Charles March, Lauren Marsolier, Edgar Martins, Didier Massard, Chris McCaw, Dodo Jin Ming, Richard Misrach, Brad Moore, Richard Mosse, Karin Apollonia Müller, Michael Najjar, Jürgen Nefzger, Walter Niedermayr, Simon Norfolk, Trevor Paglen, Robert Polidori, Mark Power, Giles Price, Pierre Radisic, Reiner Riedler, Simon Roberts, Kent Rogowski, Edith Roux, David Benjamin Sherry, Toshio Shibata, Matt Siber, Jem Southam, Jules Spinatsch, Jan Staller, Amy Stein, Anoek Steketee, Joel Sternfeld, John Stezaker, Jamey Stillings, Thomas Struth, Hiroshi Sugimoto, Joël Tettamanti, Pétur Thomsen, Penelope Umbrico, Burk Uzzle, Carlo Valsecchi, Levi Van Veluw, Massimo Vitali, Robert Voit, Donna J. Wan, Thomas Wrede, Harry Cory Wright, Yang Yongliang, Yao Lu.
boek